Vigilância epidemiológica em UTI pediátrica e de MRSA em Hospital de Assistência Terciária do Estado de Minas Gerais - Porto, Juliana Pena (2012)
Healthcare-associated infections (HAI) represent a major cause of morbidity, mortality and costs, principally those caused by bacteria resistant and multiresistant to antibiotics. The present study evaluates the epidemiology and pathogenesis of HAI in the Pediatric Intensive Care Unit (PICU), as well as in patients with infections caused by S. aureus in a tertiary-care teaching hospital, focusing on incidence rates and epidemiological indicators, density of use of antibiotics, risk factors for development of these infections and associated mortality to Methicillin-resistant Staphylococcus aureus (MRSA). The study included National Helathycare Safety Network (NHSN) surveillance (prospective, longitudinal) of patients in PICU of Hospital de Clínicas of the Federal University of Uberlândia (HC-UFU), the samples were recovered from the microbiology laboratory of the hospital, and evaluation of risk factors was made through a case (patients with HAI) versus control (patients without infection) study, from August/2009 to August/2010. An individual form of surveillance, with epidemiological, clinical and microbiological data from patients with S. aureus infections was filed. We recovered 255 isolates of S. aureus obtained from 230 patients, identified by the microbiology laboratory of the HC-UFU, from January to December 2010. We conducted a case-control matched study to assess associated mortality rates by MRSA, considering only patients with bloodstream infection (BSI). The study was approved by the Research Ethics Committee of the University (no003/11). HAI were a significant cause of morbidity in patients in the PICU, with a rate of 26.7 nosocomial infections per 1000 patient-days. Sepsis (19.6/1000 patient-days) was the most common infection, and 44.1% of the patients with sepsis had primary sepsis, and the main source of these infection were CVC or unknown, while in the secondary sepsis, lung and urinary tract were more frequent sources (8.8% each). Univariate analysis of risk factors for HAI showed the following: use of CVC (p = 0.01), use of more than two antibiotics (p <0.001), length of stay (p <0.0001) and ASIS V score (p <0.001), the first two being independent for the development of HAIS. Among the 15 cases of bloodstream infections associated with CVC, 40.0% were related to the use of this device. The high density of antibiotic use was not related to a decrease in the incidence of HAI in the investigated period. The evaluation of S. aureus in the hospital showed that 29.8% was MRSA. The epidemiological indicators showed an infection rate of 40.5 per 1000 patientdays. Sepsis was the most common infection in the investigated period. The use of antibiotics was not related to increased incidence of nosocomial infection by MRSA/1000 patient-days. Analyzing the risk factors, only the prior use of antibiotics (p <0.001) was an independent factor for MRSA infection. The hospital mortality was significantly higher among patients who had MRSA infection. The associated mortality rate of patients with MRSA BSI was 50.0% (p = 0.0134). The rate of HAI in the pediatric ICU was high (22.0%), with the majority acquired in the unit and represented by the family of Enterobacteriaceae as main agents. Sepsis was the most common cause of HAI in both, PICU and S.aureus infections in the hospital, with significant association with invasive devices. Our data suggest that methicillin resistance may be related with increased associated mortality to the microorganism among patients who acquired nosocomial bloodstream infection by S.aureus.